Maternal Mental Health and Sociodemographic Determinants of Child Nutrition Under Five Years (Journal of Tikapur Multiple Campus, 2026)
The study was conducted in Lamkichuha Municipality, Kailali District, Nepal. The main objective of this study was to examine the relationship between maternal mental health and sociodemographic determinants of child nutrition under five in the study area. This study used a cross-sectional design to collect data from 203 mothers and their children under five years. The collected data were analyzed in descriptive and inferential phases. The children surveyed had a high rate of malnutrition, with over 50 percent of children were stunted, 7 percent were underweighted, and 5 percent were wasted, respectively. Nearly 40 percent of the mothers were noted to have common mental disorders, and in the inferential analysis, there were stunting associations with ethnicity and other socioeconomic factors. Low​‍​‌‍​‍‌​‍​‌‍​‍‌ birth weight was the main factor that led to wasting. Thus, the findings highlight the important socio-economic and psycho-social factors, with maternal mental health as the most influential one in the nutrition of children. Along with child nutrition programs, the study also suggests the use of strategies that target the root causes of social determinants to be able to effectively reduce undernutrition in rural and semi-urban areas. One such intervention could be the implementation of routine maternal mental health ​‍​‌‍​‍‌​‍​‌‍​‍‌screening.